Constructive Tensor Field Theory - Rivasseau, V. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We provide an up-to-date review of the recent constructive program for field theories of the vector, matrix and tensor type, focusing not on the models themselves but on the mathematical tools used.